Harnessing Social Media for Political Socialization to Boost Youth Participation in Society 5.0 - Yogi Yoga Swara; Prayoga Bestari; Supriyono Supriyono; Junaidi Junaidi; Dedeh Nurhayati; Mulia Sari (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Social media has become a dominant digital environment for political communication and civic engagement, particularly among young people who represent the largest proportion of voters in Indonesia. However, despite widespread digital connectivity, youth political participation remains inconsistent, highlighting the need to better understand the role of social media in political socialization within the Society 5.0 framework. This study aims to examine how social media contributes to strengthening youth political participation through political socialization. A qualitative literature review was conducted by systematically analyzing peer-reviewed journal articles, academic books, official reports, and publicly accessible digital sources related to social media, political participation, and Society 5.0. The collected data were analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, thematic coding, interpretation, and verification. The findings indicate that social media facilitates political learning by expanding access to political information, encouraging interactive civic dialogue, and promoting democratic engagement among young citizens. Platforms such as YouTube, Instagram, TikTok, and AI-assisted political communication initiatives demonstrate considerable potential to strengthen political awareness when supported by credible information and adequate digital literacy. This study contributes to the literature by integrating political socialization, digital political communication, and the Society 5.0 perspective into a comprehensive conceptual framework while providing practical insights for policymakers, educational institutions, electoral management bodies, and civil society organizations in designing more effective digital political education strategies.